Aesthetic Judgments, Evaluative Content, and (Hybrid) Expressivism - Jochen Briesen (Ergo, An Open Access Journal of Philosophy)
Aesthetic statements of the form ‘X is beautiful’ are evaluative; they indicate the speaker’s positive affective attitude regarding X. Why is this so? Is the evaluative content part of the truth conditions, or is it a pragmatic phenomenon (i.e. presupposition, implicature)? First, I argue that semantic approaches as well as these pragmatic ones cannot satisfactorily explain the evaluativity of aesthetic statements. Second, I offer a positive proposal based on a speech-act theoretical version of hybrid expressivism, which states that, with the literal utterance of ‘X is beautiful’, we perform two illocutionary acts simultaneously, an assertive and an expressive one. I will specify this theory in detail and argue that it can satisfactorily account for the evaluative content of aesthetic statements. I will also discuss the advantages of the theory over other variants of expressivism in meta-aesthetics.